The Obstacles of Serbia in Obtaining the European Union Membership Status - Firmansyah, Firmansyah; Muhammad, Ali (POLITEA, 2020)
The European Union (EU) is an intergovernmental and supranational organization enlarging its membership since its formation. Due to the benefits, neighboring European countries are volunteering to join the EU. One of the EU candidate member countries is Serbia. In the process of gaining the status of EU candidate country, Serbia has faced many challenges and yet to fulfill the Copenhagen criteria as the conditions of membership by transforming and strengthening democracy. In the economic field, it is struggling to develop free markets and the rule of law. Serbia has collaborated with the International Criminal Tribunal for the Former Yugoslavia (ICTY) to process the war criminals in the past. Serbia succeeded in obtaining the status of candidate membership of the EU on March 1, 2012, which then became its new chapter.